Read and edit Góngora in the Golden Century: Martín de Angulo or the Forge (Frustrated) of a song of Author - Francisco J. Escobar (Edad de Oro, 2018)
Abstract: The present study offers a monographic analysis of the unpublished manuscript Varias poesías y casi todas las que compuso… D. Luis de Góngora, Martín de Angulo y Pulgar, guarded at the Fundación Bartolomé March (B87-V3-10). With a date of 1639-1640, it constitutes a kind of poetry songbook or anthology prepared by this author with the aim of spreading the work of Góngora, canonizing it and, in turn, position himself, with respect to the large gallery or cast of commentator scholars, in a privileged place of the Republic of letters. However, despite challenging the previous editors of Góngora and even enter into interpretative discord with other prominent actants of the literary polemic, for its ambitious fuste, the project would end unfinished and without reaching a good publishing port. Keywords: Luis de Góngora, Martín de Angulo y Pulgar, controversy about Góngora, poetry songbook, Golden Age.